Adaptive Village Head Leadership in Community-Based Tourism Governance: Gintangan Bamboo Craft Tourist Village Case Banyuwangi - Raniah Salsabila; Andhika Wahyudiono; Herwin Kurniadi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The governance of craft-based tourism villages requires adaptive leadership that simultaneously motivates artisans, drives innovation, and secures resources under fiscal volatility. Previous research has examined village head leadership roles in isolation, without integrating Sondang P. Siagian’s three functions in a context of sudden budget reprioritisation and external resource mobilisation for bamboo craft tourism. This study aims to analyse how the Gintangan Village Head enacts the motivator, innovator, and facilitator roles and utilises Corporate Social Responsibility (CSR) funding to offset a village budget reduction, thereby developing a new adaptive facilitation framework. A qualitative case study approach was employed, involving in-depth interviews with the village head, the Tourism Awareness Group chairperson, and fifteen artisans, complemented by participatory observation and document analysis. Results indicate that the innovator role, epitomised by the Gintangan Bamboo Festival, strongly enhances destination branding; however, the motivator role is undermined by information asymmetry that excludes independent artisans, and the facilitator role creatively channels CSR to sustain infrastructure development. The study concludes that inclusive communication systems, formalised CSR partnerships, and off-peak tourism programming are essential for equitable benefit distribution and long-term resilience of village tourism governance.